Hubungan Math Anxiety Dengan Hasil Belajar Matematika Siswa Kelas Tinggi Sd Inpres Perumnas Antang I - Alfina Damayanti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aimed to describe the level of mathematics anxiety, students' mathematics learning outcomes, and to analyze the relationship between mathematics anxiety and mathematics learning outcomes among upper-grade students at SD Inpres Perumnas Antang I. This research employed a quantitative approach with a correlational research design. The sample consisted of 77 upper-grade students selected through purposive sampling. Data were collected using a 20-item Mathematics Anxiety Questionnaire and documentation of students' Mathematics Midterm Examination (UTS) scores. The data were analyzed using descriptive statistics and the Product Moment correlation test. The results revealed that the students' mathematics anxiety was in the high category, with a percentage of 71.11%, while their mathematics learning outcomes were in the low category, with a percentage of 36.36%. The analysis indicated that the data were normally distributed and had a linear relationship. Furthermore, the correlation test showed a significant relationship between mathematics anxiety and mathematics learning outcomes. The higher the level of mathematics anxiety experienced by students, the lower their mathematics learning outcomes. These findings indicate that mathematics anxiety is one of the factors influencing students' achievement in mathematics.